The Role of Educational Leadership in Addressing Academic Problems Faced by the Students at Prince Sattam Bin Abdulaziz University (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this research is to reveal the role of educational leadership in the face of academic problems faced by female students of the Faculty of Sciences and Humanities in Salil at Prince Sattam Bin Abdul Aziz University. The prescriptive curriculum was used to suit the subject of the study, and the study community is made up of all female students of the Faculty of Sciences and Humanities in El Salil at the University of Prince Sattam bin Abdul Aziz. A simple randomized controlled sample of female first-graders was selected, numbering 112 students. The researcher developed a special questionnaire to find out the problems facing students at the University of Prince Sattam bin Abdulaziz. The final form of the resolution consisted of (34) paragraphs, and the response was designed to identify on the basis of the Likert quinquennial scale. The results of the study reached a high level of management leadership exercise of educational leadership functions at the Faculty of Sciences and Humanitarian Studies in Salil at the University of Prince Sattam Bin Abdul Aziz from the perspective of the study sample individuals s School of Sciences and Humanitarian Studies with a descendant at the University of Prince Sattam Bin Abdulaziz from the perspective of the study sample, The presence of an average level of curriculum problems was one of the dimensions of academic problems facing female students of the Faculty of Sciences and Humanities in Salil at the University of Princ Sattam Bin Abdulaziz from the perspective of the study sample. In the light of the results of the study, the researcher recommended that work should be done to maintain the outstanding level of educational leadership at the Faculty of Sciences and Humanities in Salil at the University of Prince Sattam Bin Abdulaziz by providing programs and training courses for leaders and familiarizing them with the most important theories and recent developments in the field of leadership.